HUBUNGAN TINGKAT STRES DENGAN SIKLUS MENSTRUASI PADA MAHASISWI PROGRAM PENDIDIKAN PROFESI DOKTER FAKULTAS KEDOKTERAN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA - KURNIA ALDIBA; DONA WIRNIATY (LP2MTBM MAKARIOZ, 2023)
Menstruation is a periodic and physiologically discharge of blood and mucosal tissue through the vagina from the uterus. Physiologically changes in the endometrium that recur at regular intervals during reproduction are called menstrual cycle. The menstrual cycle is usually influenced by several factors such as nutritional status, body mass index (BMI), physical activity, hormonal contraception and stress. Based on this description, this research aims to find out the relationship of stress levels with the menstrual cycle in doctor profession educational programs at the Faculty of Medicine University of Muhammadiyah North Sumatra. This type of research is analytical observational with a cross sectional design, using purposive sampling technique, there were 110 respondents who met the inclusion and exclusion criteria. The research result have been analyzed using Chi-Square test. Based on the result of the Chi-Square test, the result of the P Value showed 0.000, which means P Value <0.005, so it can be concluded that there is a significant relationship between stress levels and menstrual cycle of female students of the doctor profession educational program at the Faculty of Medicine University of Muhammadiyah North Sumatra. There is a significant relationship between stress levels and menstrual cycle of female medical professional education program students, Faculty of Medicine University of Muhammadiyah North Sumatra. Keyword : Stress levels, menstrual cycle, medical students